Corak Epistemologi Mistis Neoplatonisme dalam Mistisisme Islam - Sahjad M Aksan (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2018)
Mysticism is an inner struggle in search of light, clues and a way of chatting with the inner realm to reach knowledge through enlightenment. However, epistemically, mysticism is very personal, therefore it cannot be scientifically accountable. In the hands of Plotinus, mysticism seems to be living with its philosophical nuances, so that it is easily explained and adapted as one of the objects of philosophical study. Until now the legacy of the philosophy of Neoplatonism is still exists not only in the academy area, but also penetrated and became the understanding held by some Muslims who engaged in the world of Sufism both philosophical and moral. This indicates that there is freedom to have the people's horizons that can be adopted from anywhere while at the same time indicating the colors of Islamic thought. Understanding mysticism in Islam should indeed not be muzzled for any reason or to be confronted with Islamic understanding that is fiqh or fiqh oriented. Because, exploring Islamic mysticism which is recognized is influenced by the teachings of Neoplatonism, proves and teaches the people that there is a strong relationship between the conception of Shari'a and the conception of Sufism about worship so that they do not need to be contested because they have indicators that perfect the essence of tawhid and worship.